Kajian Aspek-Aspek Pesantren Tahfidz Khusus Putri di Kabupaten Deli Serdang Dengan Pendekatan Arsitektur Islam - Siti Aisyah; Wahyuni Zahra (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Education plays an important role in the progress of a nation, the high number of Islamic communities in Indonesia, including in Deli Serdang Regency, can be ensured that Muslims in Indonesia have an important role in the progress of a nation. Professor Toshiko Kinosita stated that Indonesia's human resources are still very weak to support industrial and economic development, the reason is because the government has never placed education as the most important priority, there are still various education problems that have not been resolved, such as limited education funds. , shortage of teaching materials, low number of skilled teaching staff, and inadequate facilities. To advance the nation's education, development is needed both in terms of physical and learning methods. Therefore, one effective solution is to build a Tahfidz Islamic Boarding School based on General Education. The development of science requires society to choose between focusing on knowledge in the field of religion or academics in general. Often people dream of mastering balanced knowledge, but many schools only focus education on one scientific field and reduce the quota in other fields so that knowledge becomes unbalanced. Tahfidz Islamic Boarding School is designed to provide knowledge and comfort in the learning process, equipped with adequate facilities and infrastructure as well as a more aesthetic building shape. This research aims to analyze the challenges and obstacles in developing the Tahfidz Islamic Boarding School based on General Education, and develop an inclusive and friendly solution environment. The focus is on meeting the needs of varying user abilities, while ensuring good accessibility and sustainability. In the design, building design innovations are also proposed to achieve this goal, taking into account aesthetics and Islamic values ​​in accordance with the function of the building. The methods used include mixed qualitative methods with observation, comparative studies, case studies, interviews and document analysis. The building which applies Islamic architectural concepts in the design of the Tahfidz Islamic Boarding School will also consider Islamic aesthetics and values ​​in its application.